Band structure engineering through van der Waals heterostructing superlattices of two‐dimensional transition metal dichalcogenides. Issue 2 (4th October 2020) - Zhao, Xin‐Gang; Shi, Zhiming; Wang, Xinjiang; Zou, Hongshuai; Fu, Yuhao; Zhang, Lijun
Abstract: The indirect‐to‐direct band‐gap transition in transition metal dichalcogenides (TMDCs) from bulk to monolayer, accompanying with other unique properties of two‐dimensional materials, has endowed them great potential in optoelectronic devices. The easy transferability and feasible epitaxial growth pave a promising way to further tune the optical properties by constructing van der Waals heterostructures. Here, we performed a systematic high‐throughput first‐principles study of electronic structure and optical properties of the layer‐by‐layer stacking TMDCs heterostructing superlattices, with the configuration space of [(MX2 ) n (M′X′2 )10− n ] (M/M′ = Cr, Mo, W; X/X′ = S, Se, Te; n = 0‐10). Our calculations involving long‐range dispersive interaction show that the indirect‐to‐direct band‐gap transition or even semiconductor‐to‐metal transition can be realized by changing component compositions of superlattices. Further analysis indicates that the indirect‐to‐direct band‐gap transition can be ascribed to the in‐plane strain induced by lattice mismatch. The semiconductor‐to‐metal transition may be attributed to the band offset among different components that is modified by the in‐plane strain. The superlattices with direct band‐gap show quite weak band‐gap optical transition because of the spacial separation of the electronic states involved. In general, the layers stacking‐order of superlattices results in a small up to 0.2 eV band gap fluctuation because of the built‐in potential. Our results provide useful guidance for engineering band structure and optical properties in TMDCs heterostructing superlattices. Abstract : The electronic structures of the layer‐by‐layer stacking transition metal dichalcogenide heterostructing superlattices were investigated by first‐principles calculations. The indirect‐to‐direct band‐gap transition or even semiconductor‐to‐metal transition can be realized by changing component compositions of superlattices. These transitions are ascribed to the in‐plane strain induced by lattice mismatch and the band offset among different components.